Modelling the growth of parasitic plants - Hautier, Y; Hector, A; Vojtech, E; Purves, D; Turnbull, L (2010)
Hemiparasitic plants, such as Rhinanthus species, have substantial effects on community composition and biomass. For example, the presence of parasites often increases diversity but reduces the combined biomass of hosts and parasites by c. 25% compared with unparasitized controls. We present and test a simple model of the host-parasite interaction in which parasite growth rate is a function of host growth rate that offers a new explanation for why hemiparasitic plants reduce ecosystem productivity.2. The model predicts that the combined mass of the host-parasite system is always less than the mass of the host grown alone, because the combined biomass is dependent only on host growth rate, which is reduced by the parasite. The model also predicts that the parasite should adopt an intermediate virulence to maximize its own performance, but that the optimum virulence depends on host growth characteristics.3. The key assumption of the model is that parasite growth rate and hence parasite biomass is tightly coupled to host growth rate. We tested this assumption by measuring the performance of Rhinanthus alectorolophus, a widespread hemiparasitic annual plant, on nine common European grass species. First, we determined size-corrected growth rates for the grasses by fitting power-law growth curves to multiple-harvest data on host individuals grown without Rhinanthus. Second, we grew Rhinanthus on each of the grass species and related Rhinanthus final biomass to the grass species' growth rates.4. Rhinanthus performance was strongly correlated with the growth rate of the host grass species, thus validating a key assumption of our model. However, Rhinanthus biomass on three of the nine grass species differed significantly from the value predicted based on host growth rate alone, suggesting that grass species differ in their resistance to parasitism.5. Synthesis. Parameterizing such models of the host-parasite relationship could help to explain variation in Rhinanthus performance on different hosts, variation in the effects of hemiparasites in grasslands of different productivity and differences in virulence among parasite populations. © 2010 The Authors. Journal compilation © 2010 British Ecological Society.